Binding parameters and molecular dynamics of β-lactoglobulin-vanillic acid complexation as a function of pH – Part A: Acidic pH. (30th October 2021) - Abdollahi, Kourosh; Condict, Lloyd; Hung, Andrew; Kasapis, Stefan
Highlights: Conformational alterations were observed for the protein due to the ligand addition. Bridging interactions were found between the protein and ligand via water molecules. A 1:1 binding stoichiometry was found for the protein-ligand complex at pH 2.4. The binding site in the monomer lies within the β-barrel of β-lactoglobulin. Abstract: Protein-phenolic compound interactions are commonly investigated with inappropriate linear equations for the analysis of binding strength and stoichiometry. This work utilises more appropriate protocols for the investigation of molecular interactions between vanillic acid and β-lactoglobulin at pH 2.4, where the protein predominately exists as a monomer. Non-linear binding and Job plot analysis were conducted on fluorescence data to effectively determine the interaction's dissociation constant ( K D, 2.93 × 10 −5 M) and stoichiometry (1:1). Furthermore, spectroscopic techniques revealed statistically significant alterations to the conformational characteristics of β-lactoglobulin upon complexation. Molecular dynamics (MD) simulations support a 1:1 interaction stoichiometry and reveal that the stabilisation of vanillic acid was dynamic in nature but mainly supported by four π-alkyl interactions and one hydrogen bond, located within the β-barrel of the monomer. Water molecules, which are generally not accounted for in MD simulation analysis, were shown to be an important factor in the ligand stabilization via bridging interactions.